Prevalence of Renal Pathologies in Fetuses Detected on Ultrasound in the Second Trimester of Pregnancy in Females with Oligohydramnios - Ghulam Maryam Chaudhry, Muhammad Uzair, Ghazal Noor, Drosham Raza, Seerat Tayyaba, Usama Niazi, Syed Muhammad Yousaf Farooq (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Common fetal renal abnormalities due to oligohydramnios are deficiency in the renal tissue congenitally, obstruction in the flow of urine, and reduced perfusion of renal tissue can also cause pathologies. Oligohydramnios is responsible for causing various serious fetal complications. Due to this reason, ultrasound screening in the second trimester of pregnancy is a common practice to rule out these complications. Objective: Assessment of fetal renal pathologies on ultrasound in the second trimester of pregnancy in patients with oligohydramnios Methodology: The current study is a descriptive study that was conducted in Gilani Ultrasound Centre, Ferozpur Road, Lahore from August 12, 2021, to December 14, 2021. The duration of the study was four months. A total of 149 participants were considered as a sample in the study. All the participants were in their second trimester of pregnancy and all of them were detected with oligohydramnios. According to the exclusion criteria, the patients with already present renal pathology were excluded from the study. Transabdominal ultrasound was done in all the patients with a 2-5MHz concave probe. The parameters considered for the assessment of the outcomes were gestational age (GA), estimated fetal weight (EFW), amniotic fluid index (AFI), umbilical artery Systolic/Diastolic (S/D) ratio, and findings of the fetal renal system on ultrasound. Results: A total of 149 patients in the second trimester of pregnancy, having oligohydramnios, underwent transabdominal ultrasound. 123 (82.55%) patients were not found with any fetal renal abnormalities. The remaining 26 (17.45%) had different renal pathologies such as hydronephrosis in 9 (6.04%) and infantile polycystic kidneys (PKD) in 17 (11.41%). Conclusion: The present study suggests that most of the patients with oligohydramnios had normal fetuses. Only 17.4% were detected with fetuses with renal pathologies. The most common abnormality seen was PKD and then hydronephrosis. Keywords: Second Trimester, Oligohydramnios, Infantile Polycystic Kidneys, Hydronephrosis